RADI-21. STEREOTACTIC RADIOSURGERY FOR 10 OR MORE BRAIN METASTASES PROVIDES EXCELLENT RATES OF INTRACRANIAL DISEASE CONTROL WITH SUPERIOR HIPPOCAMPAL SPARING. (12th August 2019) - Susko, Matthew; Garcia, Michael; Ma, Lijun; Nakamura, Jean; Raleigh, David; Fogh, Shannon; Golden, Encouse; Theodosopoulos, Philip; McDermott, Michael; Sneed, Penny; Braunstein, Steve
Abstract: BACKGROUND: Recent evidence supports hippocampal sparing during whole brain radiotherapy (HS-WBRT) to improve neurocognitive outcomes in patients with brain metastases (BM). This study sought to quantify the hippocampal dosimetry and treatment efficacy of stereotactic radiosurgery (SRS) to 10 or greater BM to clarify the roles of SRS and WBRT. METHODS: Patients at a single institution treated with SRS to 10 or more BM without WBRT from 1999 to 2016 were retrospectively reviewed. Treatment-related outcomes including overall survival (OS), freedom from progression (FFP), freedom from new metastases (FFNM), and adverse radiation effect (ARE) were quantified. Hippocampal volumes were retrospectively delineated and dosimetry was evaluated in patients treated with upfront SRS. RESULTS: 143 patients with a total of 2198 lesions met criteria for inclusion with 75 patients treated with upfront SRS and 68 treated as salvage from prior WBRT. Median age was 57 (IQR: 46–65) and median KPS 80 (IQR: 70–90). Histologies included breast (n=52), lung (n=49), melanoma (n=30), and other (n=12). Median number of lesions per patient was 13 (IQR 11–17) with median total volume of treatment of 4.1 cc (IQR 2.0–9.9). 12-month FFP per lesion for upfront and salvage treatment was 96.8% (95% CI: 95.5–98.1) and 83.6% (95% CI: 79.9–87.5) respectively (p < 0.001). 12-month FFNM for upfront and salvage FFSRS was 18.8% (95% CI: 10.9–32.3) versus 19.2% (95% CI: 9.7–37.8) respectively (p = 0.90). Mean hippocampal dose was 150 cGy (IQR 100–202). Symptomatic ARE was observed in 2% of patients or 1% of treated lesions. CONCLUSIONS: High rates of local control can be achieved when treating patients with greater than 10 BM with hippocampal doses that are dramatically lower than for HS-WBRT. Hippocampal sparing is readily achievable with expected rates of new metastatic lesions developing in treated patients with low rates of symptomatic ARE.